LEGAL PROTECTION OF DISADVANTAGED DEBTOR CUSTOMERS IN THE IMPLEMENTATION OF OBJECT EXECUTION AUCTION PROCEDURES IN BANK CREDIT AGREEMENTS - Disa Soraya (Indonesia Private Law Review, 2021)
In the process of granting credit, it often happens that the creditor loses when the debtor defaults so that legal rules are required in the implementation of the imposition of the mortgage as stated in a credit agreement, which aims to provide legal certainty and protection for the parties concerned. So, it raises a lawsuit for the cancellation of the auction. Based on these problems, this research aims to answer problems regarding the auction implementation of mortgage rights against debtors who are negligent by the Bank, limits on the determination of the auction limit value for the object of guarantee rights of security rights, and legal protection for bank customers for auction that does not match the value of a collateral object. This study uses an empirical juridical method by conducting literature studies and interviews with informants. The research and discussion results found that: First, the implementation of the mortgage right execution auction can be used as an alternative when bad credit occurs as a result of the customer (the debtor) in default to his creditor. The Bank, as the creditor, has the right to collect receivables from the sale of the object of the mortgage, which is guaranteed by an auction mechanism following the provisions of Law Number 4 of 1996 concerning Mortgage Rights for Land and Other Objects Related to Land. Mortgage rights in the credit agreement have a function to provide a sense of security for creditors in case of default by the debtor through the mortgage’s execution. Second, the limit value’s determination must be determined based on an appraiser’s assessment. So that if the determination of the limit value is so low, it can be used as one of the reasons for the auction’s cancellation. This is based on the provisions of Article 43 and Article 44 of the Regulation of the Minister of Finance of the Republic of Indonesia Number 27/PMK.06/2016 concerning Instructions for Conducting Auctions. Third, as a guarantee of legal protection for customers, if there is a loss due to implementing an auction that is not based on applicable legislation.